Effectiveness Therapy to Eliminate Parasite in Cattle at Teaching Factory Polytechnic State of Lampung - Vindo Rossy Pertiwi; Dwi Desmiyeni Putri; Fadli Syihabbudin (Universitas Airlangga, 2025)
Background: Gastrointestinal parasitic infections remain a significant global health concern in livestock, involving parasites from the Trematoda, Cestoda, and Nematoda classes. These infections can severely impact animal health and productivity. Purpose: This comparative study to evaluate the effectiveness of oral albendazole versus subcutaneous ivermectin in reducing gastrointestinal parasite infestations in cattle maintained at the Teaching Factory of the State Polytechnic of Lampung. Case: Eight cattle exhibited clinical signs including emaciation, dull coat, foul-smelling and dark-colored feces, with body temperatures ranging from 38.2°C to 38.6°C. Appetite and activity levels remained within normal limits. The animals had a recorded history of deworming (July 2023) and foot and mouth disease (FMD) vaccination. Case Management: Anthelmintic therapy was administered using either oral albendazole or subcutaneous ivermectin. Conclusion: Gastrointestinal and ectoparasitic infestations can lead to significant economic losses in livestock production. Subcutaneous administration of ivermectin proved to be more effective than oral albendazole in reducing gastrointestinal parasite infestation in cattle.